Reducing intracerebral hemorrhage in traumatic brain injury: Therapeutic hypothermia and intranasal insulin. - Mousavi, Shahrokh; Jahromi, Hadi Moatamed; Rafati, Ali; Zolpirani, Ardeshir Nabizadeh; Ghaffari, Mahdi Khorsand (Archives of Trauma Research)
Background: Traumatic brain injury (TBI) is a leading cause of death and disability worldwide. It consists of a primary insult that leads to secondary damage. Current TBI interventions primarily do not focus on preventive measures to improve the outcome of secondary brain injury, especially in the prehospital setting. Objectives: This study aimed to investigate the potential of therapeutic hypothermia and intranasal insulin to reduce secondary damage and prevent cerebral hemorrhage following TBI. Methods: Rats were randomly assigned to five groups: sham, TBI, TBI with insulin treatment, TBI with hypothermia treatment, and TBI with combined hypothermia and insulin treatment. Brain tissues were analyzed using histomorphological and stereological methods. Statistical analysis was conducted using the Python programming language. Results: Histomorphological analysis of brain tissue revealed no significant differences in ventricular volumes among groups. However, hemorrhages were observed, with the TBI group showing the highest hemorrhage volume. The hypothermia group showed a higher intracerebral hemorrhage compared to the sham and combined treatment groups, while the insulin group had significantly more hemorrhage than the sham group. Conclusion: Therapeutic hypothermia and intranasal insulin showed potential in reducing intracerebral hemorrhage volume post-TBI. Further research, including human clinical trials, is needed to validate these findings. This study underscores the potential benefits of therapeutic hypothermia and intranasal insulin in managing TBI-related hemorrhage and warrants further investigation.